Influence of music on work performance during joint replacement surgery, attitudes of surgical team members - Zybartaitė, Aurelija; Gedrimė, Lina (Slauga. Mokslas ir praktika, 2021)
Progress is constantly being made in almost all areas of life, including medicine. For this reason, various measures are being introduced to make any work done more efficient, easier, more productive. Music can be used in medicine, especially in the operating room, as its effect on the members of the operating team is extremely positive. And while this is acknowledged, there is not much research on this topic – the impact of music on members of the operating team.Object – is the influence of music on work performance during joint replacement, from the point of view of surgical team members.Problem – is whether music during endoprosthesis surgery can increase the productivity of surgical team members?Aim – to analyze the influence of music on the performance of work during endoprosthesis operations, from the point of view of the members of the operating team – was aimed at implementing the research objectives:1) to review the peculiarities of joint endoprosthesis operations;2) to reveal the influence of music on work in the operating room from the point of view of team members;3) to study the influence of music on the quality of work during joint arthroplasty.Methods: The method of questionnaire survey was chosen to study the attitude of the members of the operating team to the influence of music on the work productivity in the operating room. The questionnaire is considered to be the most appropriate method for explaining people’s opinions and behavior, and it is based on reliability.This was related to the aims of this study - to analyze the impact of music on performance during endoprosthesis operations. The study was conducted by submitting questionnaires to 100 members of the operating team (surgeon-operator, anesthesiologist, resuscitator, anesthesiologist, resident, anesthesia and intensive care nurse, operating nurse, and operating assistant) working in health care facilities. It should be noted that during the data collection, the members of the operational team filled in the questionnaires remotely - links to the online uploaded questionnaire were sent to each respondent. This method of conducting the study was chosen due to the current situation in Lithuania - the COVID-19 pandemic.Results of the study. The study revealed that joint replacement surgery is seen as a complicated procedure, which is complicated by team changes, because it often increases tension, affects everyone’s joint work, feels general discomfort, becomes more difficult to concentrate, increases the likelihood of errors. In order to make teamwork smoother, attention should be paid to the organization of work, the fostering of interpersonal relationships, the assessment of one’s own characteristics and peculiarities of communication, and the stronger fostering of the work environment. Music can be an effective and valuable tool for making a positive impact on operational team members. Music can help reduce anxiety, encourage relaxation, suppress the response to stressful situations, and increase the effectiveness of actions. It is very important that the music is selected in the right genre to suit the members of the operating team.
Keywords: music; productivity; joint replacement; surgery; team